Immigration-related mental health disorders in refugees 5–18 years old living in Turkey - Yalin Sapmaz Ş (Dove Medical Press, 2017)
Şermin Yalın Sapmaz,1 Bengisu Uzel Tanrıverdi,2 Masum Öztürk,1 Özge Gözaçanlar,1 Gülsüm Yörük Ülker,2 Yekta Özkan1 1Department of Child and Adolescent Psychiatry, 2Department of Psychology, Faculty of Medicine, Celal Bayar University, Manisa, Turkey Purpose: This study assessed early-onset psychiatric disorders and factors related to these disorders in a group of refugee children after immigration due to war.Materials and methods: This study was conducted between January 2016 and June 2016. Clinical interviews were conducted with 89 children and their families, and were performed by native speakers of Arabic and Persian who had been primarily educated in these languages and were living in Turkey. A strengths and difficulties questionnaire (SDQ) that had Arabic and Persian validity and reliability was applied to both children and their families. Independent variables for cases with and without a psychiatric disorder were analyzed using the χ2 test for categorical variables, Student’s t-test for those that were normally distributed, and Mann–Whitney U-test for data that were not normally distributed. Data that showed significant differences between groups who had a psychiatric disorder and on common effects in emerging psychiatric disorders were analyzed through binary logistic regression analysis.Results: A total of 89 children and adolescents were interviewed within the scope of the study. The mean age of cases was 9.96±3.98 years, and 56.2% (n=50) were girls, while 43.8% (n=39) were boys. Among these children, 47 (52.8%) had come from Syria, 27 (30.3%) from Iraq, 14 (15.7%) from Afghanistan, and 1 (1.1%) from Iran. A psychiatric disorder was found in 44 (49.4%) of the children. A total of 26 children were diagnosed with anxiety disorders, 12 with depressive disorders, 8 with trauma and related disorders, 5 with elimination disorders, 4 with attention deficit/hyperactivity disorder, and 3 with intellectual disabilities. It was determined that seeing a dead or injured person during war/emigration and the father’s unemployment increased the risk of psychopathology. The OR was 7.077 (95% CI 1.722–29.087) for having seen a dead or injured individual and 4.51 (95% GA 1.668–12.199) for father’s employment status.Conclusion: Within the context of war and emigration, these children try to cope with the negative circumstances they experience prior to migration, as well as the despair they see their parents experience. Keywords: young refugees, asylum seekers, mental health, risk factors